Layman's Report. LIFE LINES. Linear Infrastructure Networks with Ecological Solutions (LIFE14 NAT/PT/001081) - Pedroso, Nu (2022)
Thousands of animals die every year in linear transport and energy infrastructures either killed in roads or railways, or by electrocution or collision with medium and very high voltage power lines With the expanding network of transport and energy supply infrastructure in Portugal over the last decades, animal mortality became an imposing reality, assuming itself as the main non natural cause of death for animal species in many parts of the country.Additionally, the expansion of linear infrastructure networks is one of the main causes of fragmentation and loss of natural habitats, creating barriers and repelling species which contribute to further isolation of populations. Moreover, the introduction and dissemination of invasive exotic flora is often facilitated across linear infrastructure networks. Despite this, vegetated areas associated with the linear infrastructure may also be an opportunity for biodiversity conservation, promoting habitat in adverse landscape contexts and enabling animals and plants to thrive and disperse. Solutions are needed to make the presence of the linear infrastructures compatible with nature conservation!